2022
DOI: 10.1002/aoc.6844
|View full text |Cite
|
Sign up to set email alerts
|

Dicyanoargentate(I)‐based complexes induced in vivo tumor inhibition by activating apoptosis‐related pathways

Abstract: Colorectal adenocarcinoma, which often occurs as a result of a typical chromosomal instability and mismatch repair deficiencies resulting in resistance to apoptosis, is a significant burden on society. Previously, we demonstrated strong apoptosis triggers Ag(I) complexes in vitro, including [Ni (hydeten)2Ag(CN)2] [Ag (CN2].H2O (C1), [Ni (bishydeten)2] [Ag (CN)2]2.H2O (C2), and [Ni(N‐bishydeten)Ag3(CN)5] (C3), which specifically induce the apoptotic mechanism of cancer cells and selectively is non‐cytotoxic wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…demonstrated the ability of Ag(I) complexes to activate apoptosis in HT29 xenograft tumor models. This study strongly revealed that Ag(I) complexes could be a potential chemotherapeutic candidate with negligible side effects [35] . Our results indicated that K‐22 inhibited cancer cell proliferation with low IC 50 levels and stimulated apoptosis via up‐regulation of the mRNA and protein expression level of Bax/Bcl‐2 ratio in A549, Saos‐2, MCF‐7, and HT‐29 cells (Figure 2 and Figure 3, respectively).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…demonstrated the ability of Ag(I) complexes to activate apoptosis in HT29 xenograft tumor models. This study strongly revealed that Ag(I) complexes could be a potential chemotherapeutic candidate with negligible side effects [35] . Our results indicated that K‐22 inhibited cancer cell proliferation with low IC 50 levels and stimulated apoptosis via up‐regulation of the mRNA and protein expression level of Bax/Bcl‐2 ratio in A549, Saos‐2, MCF‐7, and HT‐29 cells (Figure 2 and Figure 3, respectively).…”
Section: Resultsmentioning
confidence: 61%
“…This study strongly revealed that Ag(I) complexes could be a potential chemotherapeutic candidate with negligible side effects. [35] Our results indicated that K-22 inhibited cancer cell proliferation with low IC 50 levels and stimulated apoptosis via up-regulation of the mRNA and protein expression level of Bax/Bcl-2 ratio in A549, Saos-2, MCF-7, and HT-29 cells (Figure 2 and Figure 3, respectively). It has been reported that silver metal complexes play an important role in destroying tumor cells by various mechanisms such as DNA binding and cleavage, topoisomerase enzyme inhibition, ROS generation, and induction of apoptosis.…”
Section: Resultsmentioning
confidence: 63%